CONVERGENCE AND DATA DEPENDENCE RESULTS FOR HEMICONTRACTIVE OPERATORS - Erturk, Muzeyyen; Khan, Abdul Rahim; Karakaya, Vatan; Gursoy, Faik (YOKOHAMA PUBL, 2017)
We study convergence and data dependence of iterates presented in (B. Xu and M. A. Noor, Fixed point iterations for asymptotically nonexpansive mappings in Banach spaces, J. Math. Anal. Appl. 267 (2002), 444-453.) for hemicontractive operators in the framework of a real Banach space. Some non-trivial numerical examples in a Banach space setting which is not a Hilbert space are given to show the applicability of the results obtained herein. Our results substantially improve and generalize several well-known results in the current literature.
Keywords: Convergency; iterative methods; hemicontractive operators; accretive operators; data dependence; FIXED-POINT ITERATIONS; BANACH-SPACES; MAPPINGS; SCHEME; Mathematics